2018
DOI: 10.1002/ehf2.12289
|View full text |Cite
|
Sign up to set email alerts
|

ASB1 differential methylation in ischaemic cardiomyopathy: relationship with left ventricular performance in end‐stage heart failure patients

Abstract: AimsIschaemic cardiomyopathy (ICM) leads to impaired contraction and ventricular dysfunction, causing high rates of morbidity and mortality. Epigenomics allows the identification of epigenetic signatures in human diseases. We analyse the differential epigenetic patterns of the ASB gene family in ICM patients and relate these alterations to their haemodynamic and functional status.Methods and resultsEpigenomic analysis was carried out using 16 left ventricular (LV) tissue samples, eight from ICM patients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The ASB10 association is likely specific to populations of European decent, as our AA analyses showed no evidence for association. A recent study of ischemic cardiomyopathy in a Spanish population detected significant differential DNA methylation patterns for another member of the ASB family (ASB1 gene), and further highlighted the potential role of DNA methylation of ASB family members for stroke and cardiovascular phenotypes ( Ortega et al, 2018 ).…”
Section: Discussionmentioning
confidence: 92%
“…The ASB10 association is likely specific to populations of European decent, as our AA analyses showed no evidence for association. A recent study of ischemic cardiomyopathy in a Spanish population detected significant differential DNA methylation patterns for another member of the ASB family (ASB1 gene), and further highlighted the potential role of DNA methylation of ASB family members for stroke and cardiovascular phenotypes ( Ortega et al, 2018 ).…”
Section: Discussionmentioning
confidence: 92%
“…A previous study discovered the abnormal expression of these genes in advanced-stage HF patients. 15 CUX1 plays key roles in tumour differentiation and metastasis. [16][17] Abnormal CUX1 expression is associated with the Ebstein anomaly, which affects cardiomyocytes and myocardium differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…19 In the current study, a PPI network analysis showed that ASB1 was defined as a hub gene and played important roles in PPIs in HF. ASB1 is a member of the ankyrin repeat and SOCS box-containing (ASB) family of proteins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The ASB1 gene, located on chromosome 2q37, encodes a protein with 335 amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cytokines TNFα and IL-1α can up-regulate ASB10 expression that may be involved in glaucoma pathogenesis (25). The methylation status of the ASB1 gene relates with left ventricular performance in ischemic cardiomyopathy, and the epigenetic modification of the ASB1 gene is involved in anxiety-related immune dysregulation (26,27). Recently, the structure and dynamics of the ASB9-Cul-RING E3 ligase complex were reported (28).…”
Section: Significancementioning
confidence: 99%